Global, regional, and national burden and trends of reproductive-aged male and female infertility from 1990–2021 - Zeng, Guoqiang; Liu, Lingyun; Wang, Yuantao; Yu, Jinyu; Wang, Hongliang; Li, Faping (Frontiers in Endocrinology, 2025)
BackgroundInfertility is a complex condition influenced by multiple factors and is associated with significant health and social implications. The aim of this study was to investigate the burden of infertility among reproductive-aged (15–49 years) men and women from 1990 to 2021, along with the associated trends.MethodsData on the prevalence and disability-adjusted life years (DALYs) related to infertility among 15–49 years men and women from 1990 to 2021 were obtained from the Global Burden of Disease (GBD) Study 2021. The estimated annual percentage change (EAPC) was calculated to assess the changes in age-standardized rates of prevalence (ASPR) and DALYs (ASDR). Additionally, the relationship between disease burden and the socio-demographic Index (SDI) was analyzed. Joinpoint regression analysis was employed to conduct a thorough examination of the trends for disease burden from 1990 to 2021.ResultsIn 2021, the global number of cases and DALYs for male infertility among 15–49 years increased by 74.66% and 74.64% since 1990. For females, the global number of cases and DALYs increased by 84.44% and 84.43% respectively. Among the five SDI regions, the middle SDI region recorded the highest number of cases and DALYs in 2021, accounting for approximately one-third of the global total. From an age subgroup perspective, the 35–39 age group reported the highest number of cases in 2021. The infertility disease burden was negatively correlated with SDI in national level. Joinpoint analysis demonstrated a declining trend in the annual percentage change (APC) for male infertility ASPR and ASDR during the periods 1990–2001 and 2005-2010. The ASPR time points of female infertility were slightly different from those for males, but the overall trend remained consistent.ConclusionOverall, the burden of infertility among 15–49 years men and women has significantly increased globally over the past 32 years, particularly in middle SDI regions and among the 35–39 age group. The findings underscore the importance of tailored interventions aimed at addressing infertility issues in this population, contributing to the achievement of the sustainable development goals established by the World Health Organization.